Following the Francis report: Investigating patient experience of mental health in-patient care. (July 2016) - Csipke, E.; Williams, P.; Rose, D.; Koeser, L.; McCrone, P.; Wykes, T.; Craig, T.
Abstract : Background: The Francis report highlights perceptions of care that are affected by different factors including ward structures. Aims: To assess patient and staff perceptions of psychiatric in-patient wards over time. Method: Patient and staff perceptions of in-patient psychiatric wards were assessed over 18 months. We also investigated whether the type of ward or service structure affected these perceptions. We included triage and routine care. The goal was to include at least 50% of eligible patients and staff. Results: The most dramatic change was a significant deterioration in all experiences over the courseof the study. Systems of care or specific wards did not affect patient experience but staff were more dissatisfied in the triage system. Conclusions: This is the first report of deterioration in perceptions of the therapeutic in-patient environment that has been captured in a rigorous way. It may reflect contemporaneous experiences across the National Health Service of budget reductions and increased throughput. The ward systems we investigated did not improve patient experience and triage may have been detrimental to staff.